Heroic female images in «The book of my grandfather Korkud» (Journal of Philosophy Culture and Political Science, 2015)
The «female history» described in a written monument of medievalTurkic culture «The book of my grandfather Korkud» is given in the article.Alongside with history of wars and attacks of sultans and leaders of tribesof oguz «The female history» is represented in it as well. The image of thepowerful maiden, known in the powerful fairy tale and the heroic epos,is represented as a female ideal of the nomadic and semi-nomadic Turkicpeople. The evolution of a female image reflected in legends, legends andmyths of the Turkic people is traced in the article. Archaism of a femaleimage of ancient stories of the Turkic people is emphasized in this publication.Realistic character of a female ideal of the epos of Turkic peoplesat the time of the storyteller’ life and musician – Korkut-At is traced in thearticle on materials of the epos of oguz, historical sources and scientificpublications. The female ideal of the epos of oguz is caused by a way oflife of Turkic peoples in which war was «honourable occupation», «somekind of sport», this fact is noted in the article.
Keywords: ancient powerful fairy tale; Turkic heroic epos; «a female subject» as history of powerful maidens and history of «the captured woman»; «crying» of women; the woman – «with – the ruler» and the keeper of the family center.